Steroids in treatment of pertussis: A controlled clinical trial. Issue 1 (January 1973) - Zoumboulakis, D.; Anagnostakis, D.; Albanis, V.; Matsaniotis, N.
Abstract : Of 135 children with pertussis 70 were treated with steroids for 7 to 8 days and the remainder served as controls. The two groups were comparable. All children received erythromycin for 10 days. They were in the first week of the paroxysmal stage. Coughing, whooping, and vomiting episodes occurred less frequently in the steroid-treated groups, and the illness was shorter especially in babies under 1 year of age. These results indicate that steroids may have a beneficial effect on the course of pertussis if given early in the paroxysmal stage. Nevertheless, since steroids are potentially dangerous drugs we believe their use in pertussis must be limited to severe cases, particularly in infants under 6 to 9 months of age where the mortality is highest.